2019
DOI: 10.3201/eid2512.181513
|View full text |Cite
|
Sign up to set email alerts
|

Human Infection with Orf Virus and Description of Its Whole Genome, France, 2017

Abstract: Zoonotic transmission of parapoxvirus from animals to humans has been reported; clinical manifestations are skin lesions on the fingers and hands after contact with infected animals. We report a human infection clinically suspected as being ecthyma contagiosum. The patient, a 65-year-old woman, had 3 nodules on her hands. She reported contact with a sheep during the Aïd-el-Fitr festival in France during 2017. We isolated the parapoxvirus orf virus from these nodules by using a nonconventional cell and sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
4
23
2
Order By: Relevance
“…The phylogenetic tree (of complete genome) showed the six goat ORFVs and seven sheep ORFVs formed distinctly separate branches except for Ger/D1701. Interestingly, this result slightly deviated from recently studied phylogenetic analysis based on the complete genome, which forms two host-specific clades (Andreani et al;Zhong et al, 2019). However, our analysis in comparison to the previous study, showed increase the heterogeneity and unable to maintain the perfection of the host-specific clade.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The phylogenetic tree (of complete genome) showed the six goat ORFVs and seven sheep ORFVs formed distinctly separate branches except for Ger/D1701. Interestingly, this result slightly deviated from recently studied phylogenetic analysis based on the complete genome, which forms two host-specific clades (Andreani et al;Zhong et al, 2019). However, our analysis in comparison to the previous study, showed increase the heterogeneity and unable to maintain the perfection of the host-specific clade.…”
Section: Discussioncontrasting
confidence: 87%
“…The morbidity rate often reaches up to 100%, resulting in loss of body weight in adults, and feebler kids, thereby negatively affecting the herd economy (Haig & Mercer, 1998). Zoonosis leads to infections in animal handlers by forming painful lesions in hand and can spread to other organs like face and genitals (Andreani et al;Duchateau, Aerts, & Lambert, 2013;Rajkomar, Hannah, Coulson, Owen, & dermatology, 2016;Turk, Senturk, Dereli, & Yaman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even within the same family, viruses have similar replication or life-cycle strategies, but may show different GC frequencies [48]. Although high GC amplification could have fixed erroneous base calls in the sequencing in an unpatterned and uneven manner, which might influence sequences reported and downstream analyses, we retrieved enough sequences and got the same conclusion with prior researches, which all indicated that the biological relevance of G/C richness and frequency [6,49,50].…”
Section: Discussionmentioning
confidence: 58%
“…In that same paper, the authors address insect vectors as potential vectors of LSDV and even make a case that suggests house flies might play a role. As for the practical aspects of the ORF virus, we must focus not only on the economics of this virus [31], but also on its role as an important emerging infectious disease [2,32,33] both in sheep/goat hosts and with respect to its zoonosis and the infection of humans [34]. The persistence of the ORF virus in the environment, as well as in hosts, creates an ever-increasing contact for zoonoses or spillover into the human population.…”
Section: Discussionmentioning
confidence: 99%